A Systematic Review of Single-Case Research on Video Analysis as Professional Development for Special Educators - Morin, Kristi L.; Ganz, Jennifer B.; Vannest, Kimberly J.; Haas, April N.; Nagro, Sarah A.; Peltier, Corey J.; Fuller, Marcus C.; Ura, Sara K. (The Journal of special education, 2019)
Studies using video analysis are being reported more frequently in the literature. Although the body of research suggests that video analysis is effective for changing educators’ instructional practices, questions regarding for whom and under what circumstances it is most effective still remain. This meta-analysis reports on the overall effectiveness of video analysis when used with special educators, as well as on moderator analyses related to participant and instructional characteristics. Tau-U, a nonparametric effect size commonly used in single-case research, was used to aggregate the results from 191 AB phase contrasts across 12 dissertations and 18 peer-reviewed publications. A total of 111 participants across 69 single-case design experiments are reflected in the results. Overall, results indicate that video analysis is effective for changing the instructional practices of special educators and that it can be used across a variety of settings and with a diverse group of educators.